The electrophysiological features of X-linked juvenile retinoschisis in a young male: a case report. Issue 1 (January 2022) - Yan, Weiming; Wang, Yunpeng; Ye, Qian; Chen, Xiaohong; Chen, Yanjin; Jiang, Chuan; Chen, Meizhu
This case report describes the detailed electrophysiological features and the corresponding relationship with the structural changes in a case of X-linked juvenile retinoschisis (XLRS). A 25-year-old male presented with a history of several years of decreased visual acuity in both eyes. The best corrected visual acuity was 20/200 in oculus dexter (OD) and 20/80 in oculus sinister. Retinoschisis was found in the macula by optical coherence tomography, which was more severe in OD. Electroretinogram revealed a similar electronegative waveform in both eyes. Visual evoked potential detected a reduced amplitude and delayed phase in P100-wave, which was worse in OD. The patient was diagnosed as XLRS and advised to undergo continuous medical observation. He was followed up for the next year, with no significant change in retinal function and structure being observed. These current findings suggest that electrophysiology permits the detailed analysis of the clinical picture of XLRS and helps to gain a deeper understanding of the pathogenesis.